2001
DOI: 10.1209/epl/i2001-00515-8
|View full text |Cite
|
Sign up to set email alerts
|

Phonon band structures and resonant scattering in Na 8 Si 46 and Cs 8 Sn 44 clathrates

Abstract: The low and glasslike thermal conductivity of metal-doped semiconductor clathrate compounds makes them potentially high-efficiency thermoelectric materials. The cause of this unique and remarkable property has been postulated to be due to resonant scattering of lattice phonons by localized vibrations of the dopants. We present theoretical evidence in support of this hypothesis through the analysis of electronic and vibrational interactions between dopant atoms with the host framework. In particular, the contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
25
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 34 publications
5
25
0
1
Order By: Relevance
“…This structure character results in a remarkable feature in phonon dispersion, as show in Figure 2A, that is the existence of the hybridized modes with frequency ω h as a result of the so-called avoided crossing between the acoustic phonon mode in the host system and the flat guest modes (Nakayama and Kaneshita, 2011). Previous studies (Tse et al, 2001;Pailhès et al, 2014) claimed that the hybridized modes are caused by the rattling of Ba(2) atom in the large cage, which is also confirmed by our calculation of phonon density of states (DOS) in Figure 2B. Moreover, we find that DOS for Ba(2) atom is mainly distributed in the lowfrequency region (below 2.5 THz), and is almost separated with the DOS peaks for the host Si atom.…”
Section: Resultsmentioning
confidence: 79%
“…This structure character results in a remarkable feature in phonon dispersion, as show in Figure 2A, that is the existence of the hybridized modes with frequency ω h as a result of the so-called avoided crossing between the acoustic phonon mode in the host system and the flat guest modes (Nakayama and Kaneshita, 2011). Previous studies (Tse et al, 2001;Pailhès et al, 2014) claimed that the hybridized modes are caused by the rattling of Ba(2) atom in the large cage, which is also confirmed by our calculation of phonon density of states (DOS) in Figure 2B. Moreover, we find that DOS for Ba(2) atom is mainly distributed in the lowfrequency region (below 2.5 THz), and is almost separated with the DOS peaks for the host Si atom.…”
Section: Resultsmentioning
confidence: 79%
“…Similar to the known clathrate phases at high doping levels, these compounds are calculated to have low values of S at 300 K of about 5 ± 10 mV K À1 and thus would not be useful thermoelectrics. [9,40,44,45] As in our previous study [9] it was found that an estimate of S for variable concentrations can be obtained by assuming a rigid-band model (derived from the empty cage) and monitoring S as a function of increasing Fermi energy. This is done by filling the empty orbitals of the vacant lattice with e electrons, which artificially increases the Fermi level, and recalculating S. This function is plotted for three such hypothetical band fillings for the Si 40 lattice in Figure 8.…”
Section: Resultsmentioning
confidence: 85%
“…Specifically, we sought alternatives to the experimental structures, [22±29] determined the amount of electropositive metal dopant needed to stabilize these phases, and determined whether they have desirable thermoelectric properties. Note that in these compounds resonant phonon scattering, [9,44,45] in which the localized vibrations of the dopant atom couple with the phonon modes of the clathrate framework, can lower the overall thermal conductivity, and this makes them desirable for practical application. This mechanism was shown to be operational in known Na ± Si compounds [9] and is likely to also occur in similar species.…”
Section: Resultsmentioning
confidence: 99%
“…Details of the computational procedure have been reported previously on similar clathrate systems [14,15]. The starting atomic coordinates were taken from experiment.…”
mentioning
confidence: 99%